Ausländische Werkvertragsarbeitnehmer am Bau: Bauboom oder Verdrängungswettbewerb? - Jörn-Steffen Pischke; Johannes Velling (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1993)
While the entry of new immigrants into the German labour market is usually controlled by the local labour authorities, no such controls exist for contract workers (Werkvertragsarbeitnehmer), who are subject to national quotas which are fixed in the medium term. Therefore the ease of contract workers is especially suited to examine the question of substitution between domestic and foreign workers. We focus on the construction sector where there was an immense inflow of contract workers in the past three years. While the sudden entry of a large number of foreign construction workers due to the opening of eastern borders might have had detrimental effects on employment and wages of natives it is also possible that much of the inflow was due to strong labour demand caused by the boom in the construction sector. Although it is not possible to distinguish cleanly between these hypotheses, the evolution of standard labour market indicators such as total employment, the unemployment rate, the number of vacancies, and contract wages during the past five years show that this labour market segment might have suffered from a labour shortage in 1990 and 1991 if no foreign workers had been allowed to enter.
Keywords: 330; Bauberufe; Internationale Arbeitsmobilität; Deutschland